Variations in Lorica Morphology and Element Composition in the Euglenoid Trachelomonas hispida var. coronata Under the Influence of Fe and Mn Supply - Małgorzata Poniewozik; Mateusz Kudlak; Emil Zięba (Cellular Microbiology)
Trachelomonas hispida var. coronata is one of the most widely reported varieties of T. hispida from water bodies worldwide. The specimens of this variety, apart from their species-specific features, such as an ellipsoidal lorica covered with strong, sharp spines, have a crown consisting of long spines surrounding the apical pore opening. The process of lorica formation is poorly understood, and in the few studies dealing with this topic, results indicate that these taxa and the entire species can produce lorica completely devoid of spines, a diacritic feature of the species. In our study, we observed in detail the formation process of the lorica in this taxon under different chemical conditions in relation to the concentration of the basic elements, Fe and Mn, which are saturated in trachelomonad lorica. The results showed that in the Fe-enriched medium, monads formed delicate, porous, spiny envelopes, whereas in the Mn-enriched medium, the loricae were more solid and less porous and had weaker developed spines; rather, they were in the form of short papillae. Differences were also observed in the structure surrounding the apical pore, which was developed differently in the two sets of media modifications (Fe- or Mn-supplemented media). We also observed different elemental compositions and colouration of loricae of cells growing in different media. This revealed that the features considered during the process of species identification are very unstable making the entire exercise highly complicated. Our research also shows that a broad discussion of the problem should be undertaken, and modern methods must be developed to unravel the complexities not only within the species but also within the entire Trachelomonas.